Marketing Strategy Analysis of Neutron Tutoriang Banjarmasin in Indonesia’s Nonformal Education Sector - Yudhyani, Eka; Ali, Wasir (Journal of Nonformal Education, 2025)
Background: Competition in the tutoring industry in Indonesia is increasing along with the increasing demand for quality education outside of formal school. In this context, Neutron Tutoring Banjarmasin faces the challenge of not only attracting new students but also maintaining the loyalty of existing students. Research Urgency: The urgency of this research lies in the importance of understanding how Neutron Banjarmasin responds to the increasingly competitive tutoring industry. With many options available to students and parents, effective marketing strategies have become essential. The findings of this study are expected to provide practical guidance for similar institutions, especially in the post-pandemic era that demands digital adaptation and hybrid learning. Research Objectives: This study aims to analyze the marketing strategies implemented by Neutron Banjarmasin Tutoring in order to attract and retain students in the midst of fierce industry competition. Research Method: Through a qualitative approach with a case study design, this study collects data through interviews with management, surveys of students, and analysis of digital marketing media channels used. Research Findings: The results show that digital marketing, referral programs, and service personalization contribute significantly to the increase in the number of new students and customer loyalty. The use of social media and paid advertising has a positive impact, while a personalized approach to service increases student satisfaction. Research Conclusion: Neutron Tutoring Banjarmasin has demonstrated that an integrated marketing strategy combining digital presence, personal engagement, and community-based referrals can effectively address challenges in student acquisition and loyalty. The success lies in understanding the target audience, utilizing appropriate communication channels, and continuously evaluating marketing performance. This case illustrates the importance of adapting marketing practices to both technological advancements and customer expectations. Research Novelty/ Contibution: The implications of these findings can be recommendations for other tutoring institutions in developing more effective marketing strategies focus nonformal education for tutoring.